2023
DOI: 10.3390/ijms24086972
|View full text |Cite
|
Sign up to set email alerts
|

Dual Blockade of TGF-β Receptor and Endothelin Receptor Synergistically Inhibits Angiotensin II-Induced Myofibroblast Differentiation: Role of AT1R/Gαq-Mediated TGF-β1 and ET-1 Signaling

Abstract: Angiotensin II (Ang II) upregulates transforming growth factor-beta1 (TGF-β1) and endothelin-1 (ET-1) in various types of cells, and all of them act as profibrotic mediators. However, the signal transduction of angiotensin II receptor (ATR) for upregulation of TGF-β1 and ET-1, and their effectors that play an essential role in myofibroblast differentiation, are not fully understood. Therefore, we investigated the ATR networking with TGF-β1 and ET-1 and identified the signal transduction of these mediators by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…FFAR4 activation inhibits TGF-β mediated fibrosis [ 26 ]. Several lines of evidence have demonstrated that TGF-β signaling plays a major role in fibrosis and thus inhibition of TGF-β signaling results in the suppression of fibrosis [ 96 , 97 ]. In fibroblasts, FFAR4 stimulation activates the cGMP–PKG pathway, and thus the phosphorylation of Smad3 by PKG inhibits TGF-β-mediated fibrosis [ 26 ].…”
Section: Candidate Molecular Therapeutic Targets For Hf and Cardiac R...mentioning
confidence: 99%
“…FFAR4 activation inhibits TGF-β mediated fibrosis [ 26 ]. Several lines of evidence have demonstrated that TGF-β signaling plays a major role in fibrosis and thus inhibition of TGF-β signaling results in the suppression of fibrosis [ 96 , 97 ]. In fibroblasts, FFAR4 stimulation activates the cGMP–PKG pathway, and thus the phosphorylation of Smad3 by PKG inhibits TGF-β-mediated fibrosis [ 26 ].…”
Section: Candidate Molecular Therapeutic Targets For Hf and Cardiac R...mentioning
confidence: 99%